2009
DOI: 10.24885/sab.v22i1.261
|View full text |Cite
|
Sign up to set email alerts
|

Estudo petrográfico da tecnologia cerâmica Guarani no extremo sul de sua distribuição

Abstract: Este trabalho constitui o primeiro estudo comparativo de cortes finos de cerâmica arqueológica procedente de diferentes sítios Guarani da região do rio Paraná inferior, iniciando com ele uma base cumulativa de dados. Os primeiros resultados obtidos assinalam uma similaridade significativa na composição e estrutura das pastas nos três conjuntos analisados. Igualmente, se sublinha a singularidade técnica e estilística da cerâmica Guarani e suas notáveis diferenças com àquela manufaturada pelos grupos de caçadore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
16

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 10 publications
0
3
0
16
Order By: Relevance
“…The inclusion of more or less of these small pellets of iron oxide in the analyzed samples was partly responsible for the observed variations, due to its punctuated distribution. These oxides have been identified in practically all the thin sections analyzed in the local pottery [8,11,13]. The X-ray images revealed their metallic composition [8], and recent studies with energy dispersive analysis of X-rays (EDAX) confirmed their composition (study in progress).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion of more or less of these small pellets of iron oxide in the analyzed samples was partly responsible for the observed variations, due to its punctuated distribution. These oxides have been identified in practically all the thin sections analyzed in the local pottery [8,11,13]. The X-ray images revealed their metallic composition [8], and recent studies with energy dispersive analysis of X-rays (EDAX) confirmed their composition (study in progress).…”
Section: Resultsmentioning
confidence: 99%
“…These results reinforced the observations about the presence of pellets of iron oxide as natural tempers, that manifest themselves in the pottery as hardened red lumps (Fe 3+ ). It is feasible to consider that a small fraction of them, basically the black ones, includes MnO in their composition [8,11,14]. Manganese oxide, however, was in a much lower amount than iron oxide (Table II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se han profundizado diversos aspectos del proceso de manufactura a partir de la combinación de estudios experimentales, tecnomorfológicos y microscópicos, y se ha analizado la decoración desde diferentes perspectivas. También se están explorando el uso de la alfarería, a partir de la arqueología experimental, del análisis químico y de microrrestos vegetales en residuos orgánicos, y las alteraciones postdepositacionales (Ceruti & Traver Borny 2007;Feuillet Terzaghi & Escudero 2006;Loponte 2008;Ottalagano 2009Ottalagano , 2013Pérez et al 2009Pérez et al , 2015Capdepont & Bonomo 2010Coll & Katalinich 2010;Bonomo et al 2012;Barboza & Píccoli 2013;Píccoli 2014;Di Prado 2015Píccoli & Barboza 2016;Silva 2017).…”
Section: Tecnología Cerámicaunclassified
“…Los antecedentes sobre los grupos guaraníes en nuestro país, en la zona del delta bonaerense y el estuario del Río de la Plata, tienen un acervo histórico profundo de alrededor de dos siglos, siendo a lo largo de los mismos numerosos los aportes recibidos (Burmeister 1872;Ambrosetti 1895;Torres 1911;Outes 1917Outes , 1918Maldonado Bruzzone 1931;Lothrop 1932;Vignati 1936Vignati , 1941Cigliano 1968a;Cigliano et al 1971;Caggiano y Prado 1991;Caggiano et al 2003;Loponte 2008;Loponte y Acosta 2003, 2007, 2008Rizzo y Shimko 2003;Bogan 2005;Capparelli 2005Capparelli , 2007Rodríguez 2001Rodríguez , 2004Rodríguez , 2008Mucciolo 2007;Acosta et al 2010Acosta et al a, 2010Pérez et al 2009;Acosta y Mucciolo 2009;Bognanni et al 2012;Loponte et al 2011; Capparelli y Dávila 2012; Loponte y Capparelli 2013. ).…”
Section: Introductionunclassified